Comparative Analysis of the Performance of Magnesium-Teflon-Viton (MTV) and Aluminum-Teflon-Viton (ATV) Flares - Satria Aqila Widyatama; Elda Pratita; Gunaryo Gunaryo; Minandre Wiratama; Anggaria Maharani (Indonesian Journal of Chemical Studies, 2025)
The development of effective pyrotechnic flare compositions is critical for advancing indigenous defense capabilities. This study presents a comparative analysis of two formulations, Magnesium-Teflon-Viton (MTV) and Aluminum-Teflon-Viton (ATV) to evaluate their suitability for application in decoy systems within Indonesia’s defense sector. Key performance factors, including luminosity, combustion temperature, burn rate, and spectral color distribution, were assessed through controlled laboratory experiments. The MTV composition demonstrated superior luminous intensity, reaching up to 3572.5 lux, alongside broader spectral color output, indicating enhanced visibility and potential effectiveness in visual signaling applications. Conversely, the ATV composition exhibited higher average burn rates, peaking at 5.55 g/s, which suggests greater combustion efficiency and faster energy release, advantageous for time-sensitive deployments. Both systems maintained comparable combustion temperatures, with variations attributed to compositional differences in fuel-metal interactions and binder behavior. This study emphasizes the trade-offs between brightness and combustion kinetics inherent in flare formulations and provides valuable insights for optimizing material selection according to mission-specific applications. The results obtained in this study are expected to contribute to the creation of independence in defense material development by utilizing locally available resources and promoting domestic innovation in pyrotechnic technology.